2003
DOI: 10.1029/2002jd002452
|View full text |Cite
|
Sign up to set email alerts
|

New particle formation from photooxidation of diiodomethane (CH2I2)

Abstract: [1] Photolysis of CH 2 I 2 in the presence of O 3 has been proposed as a mechanism leading to intense new particle formation in coastal areas. We report here a comprehensive laboratory chamber study of this system. Rapid homogeneous nucleation was observed over three orders of magnitude in CH 2 I 2 mixing ratio, down to a level of 15 ppt ($4 Â 10 8 molec. cm À3 ) comparable to the directly measured total gas-phase iodine species concentrations in coastal areas. After the nucleation burst, the observed aerosol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
269
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 239 publications
(289 citation statements)
references
References 69 publications
(111 reference statements)
17
269
3
Order By: Relevance
“…In fact, during the burst, the nucleation mode acts as a sink for sulphuric acid as the condensation sink rises significantly. Following detailed field studies during the research programme New Particle Formation and Fate in the Coastal Environment (PARFORCE; http://macehead.nuigalway.ie/parforce), laboratory studies into the formation of aerosols from CH 2 I 2 , conducted by Hoffmann et al (2001) and Jimenez et al (2003), confirmed significant particle production in the presence of UV-radiation and O 3 and a formation mechanism resulting in the polymerization of OIO into I 2 O 4 was proposed (figure 7). Jimenez and colleagues suggested that while it was clear that significant particle production occurred from CH 2 I 2 , an additional source of condensable material might be required to explain the observations in the atmosphere.…”
Section: Secondary Aerosol Formation From Iodine Vapoursmentioning
confidence: 99%
“…In fact, during the burst, the nucleation mode acts as a sink for sulphuric acid as the condensation sink rises significantly. Following detailed field studies during the research programme New Particle Formation and Fate in the Coastal Environment (PARFORCE; http://macehead.nuigalway.ie/parforce), laboratory studies into the formation of aerosols from CH 2 I 2 , conducted by Hoffmann et al (2001) and Jimenez et al (2003), confirmed significant particle production in the presence of UV-radiation and O 3 and a formation mechanism resulting in the polymerization of OIO into I 2 O 4 was proposed (figure 7). Jimenez and colleagues suggested that while it was clear that significant particle production occurred from CH 2 I 2 , an additional source of condensable material might be required to explain the observations in the atmosphere.…”
Section: Secondary Aerosol Formation From Iodine Vapoursmentioning
confidence: 99%
“…We have deduced previously that the nucleation precursor and nucleation processes occur near the coast only, so it is unlikely that sulfuric acid is the precursor. Field measurements at Mace Head, Ireland, and lab studies indicate that CH 2 I 2 [Makela et al, 2002;Hoffmann et al, 2001;Jimenez et al, 2003] or I 2 [Saiz-Lopez and Plane, 2004;McFiggans et al, 2004] out gassed from the ocean may be precursors for nucleation.…”
Section: Effect Of Wind Speed On Nucleationmentioning
confidence: 99%
“…The mass of key chemical components can be resolved as a function of the vacuum aerodynamic diameter of the particles (dM/dlogD va ) by averaging the time resolved ion signals after chopping the particle beam with the mechanical chopper (2% duty cycle) at the front of the second chamber. The difference between vacuum aerodynamic diameter, measured by the AMS in a free-molecular regime flow, and classical aerodynamic diameter, measured in a continuum regime flow, and their relationship with mobility diameter are discussed in Jimenez et al (2003b). In the MS mode the averaged chemical composition of the non-refractory aerosol components is determined by scanning the full mass spectrum (1-300 m/z units) with the quadrupole mass spectrometer identification and quantitative calibrations of chemical species are presented in Jimenez et al (2003a).…”
Section: Description Of the Aerodyne Amsmentioning
confidence: 99%